Review of: Pascal Firges, French Revolutionaries in the Ottoman Empire: Diplomacy, Political Culture, and the Limiting of Universal Revolution, 1792–1798 - Koutzakiotis, Georges (The Historical Review/La Revue Historique, 2019)
.